Iconographical Interpretations Of Modern Elements In Northern Bali Temple Reliefs During Dutch Colonial Period, 1900-1940 - Putra, I Dewa Alit Dwija (2023)
Relief art on temple buildings in Bali generally uses ornaments from classical Balinese Hindu cultural heritage. Traditional or classical art resulted from a blend of Javanese and Balinese Hindu culture during the Majapahit era. Since the arrival of Dutch colonialism in North Bali in 1849, it had had numerous influences and caused changes in all aspects of Balinese life. Likewise, in traditional arts, especially relief art. The shift from conventional relief art to modern art can be seen in several temple buildings in North Bali, such as Beji Sangsit Temple, Madue Karang Temple, Dalem Jagaraga Temple, and Lan Puseh Village Temple. The embodiment of reliefs shows images that differ from traditional art conventions such as theme, composition, and style. Like other works of art, reliefs are made with a specific purpose and message. This study provides a more in-depth analysis of relief art by using the iconography and iconology theory of Erwin Panofsky as a method for analysing reliefs in the context of the socio-cultural history of the Balinese people. Through three stages of Panofsky's iconographic analysis, it can be observed that the relief works were created as part of the Dutch political strategy to shape the image of Bali as an "exotic" and "cultured" area and as a world tourist destination, in addition to divert the memory of the shame caused by the war the Dutch had against the Balinese people.